A Case Study of Tertiary Students' Experiences Using Edmodo in Language Learning - Zuraina, Ali (Universiti Malaysia Pahang, 2015)
The past decade has seen the rapid development of technology in online learning. Its development has led many researchers to investigate the use of Web 2.0, where learning is present not only in the four-walls of the classroom. This paper, therefore, reports on students‟ experiences using a Web 2.0 tool, namely Edmodo. In particular, the study aims at identifying their perceptions of using the platform in language learning and their views on the possibility of using it to supplement face-to-face discussions in English language classes. The study involved 24 samples who undergone focus group interview as the method of collecting data. In general, results of the study revealed mixed reviews, where some students agreed with the use of Edmodo while others expressed negative opinions towards its use. In addition, two broad themes emerged from analysis of the data. These findings have significant implications in that the teacher, in the first place, needs to be equipped with the knowledge of using the platform to benefit the students. Nevertheless, this research extends our knowledge for the understanding of how to integrate Web 2.0 technologies in language classes.